Peran Kelembagaan terhadap Peningkatan Kapasitas Petani Aren di Kabuaten Garut - Epul, Saepul Ridwan; Adinasa, Muhamad Nu’man (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
Sugar palm or kawung is one of the leading commodities in Garut Regency. The aim of this research is to analyze the role of institutions in increasing the capacity of sugar palm farmers in Garut Regency. The sampling technique in this research uses a purposive sampling technique, with the criteria that farmers have joined an institution, data collection techniques use the interview method through questionnaires and observation. The statistical analysis tool used in this research is Scoring. The results of the research can be concluded that the role of institutions in Garut Regency is still not effective and efficient. Institutional development in increasing farmer capacity requires several appropriate approaches so that the efforts carried out are effective and efficient. However, there are several things that have a positive impact with the role of institutions in increasing the capacity of farmers in Garut Regency. Sugar palm agribusiness will experience a very significant increase if there are efforts to encourage and strengthen institutions with sugar palm farmers.